Occlus-o-Guide(® )versus Andresen activator appliance: neuromuscular evaluation - Farronato, Giampietro (Springer, 2013)
BACKGROUND: The aim of the present study was to assess the muscular variations at the electromyography (EMG) level for the anterior temporalis muscles and masseter muscles during treatment with Occlus-o-Guide(®) and Andresen activator appliances. METHODS: Eighty-two patients (35 males and 47 females) aged between 8 and 12 years (mean age, 10.5 ± 0.8 years) participated in the study. Fifty patients underwent treatment with an Occlus-o-Guide(®) and 32 patients with an Andresen activator. All patients underwent EMG examination using a Freely EMG (De Gotzen, Legnano, Italy) and surface bipolar electrodes when the appliances were worn for the first time (T0), and after 6 months (T1) and after 12 months (T2) of appliance use. RESULTS: Statistical analysis showed that both at T0 and T2, the percent overlapping coefficient (POC) of the anterior temporalis muscles was not statistically different between the appliance groups. At T0, the POC of the masseter muscles was significantly lower for the Andresen appliance as compared to the Occlus-o-Guide(®) (p = 0.02), while at T2 this significance was lost. CONCLUSIONS: At insertion of an appliance, all patients show neuromuscular balance that does not correspond to orthognathic occlusion. Both appliances work by creating muscular imbalance. With the appliances in situ, EMG responses were generally analogous for the Occlus-o-Guide(®) and the Andresen activator; however, the imbalance was greater and the recovery of the orthological muscular balance was slower in patients under treatment with the Andresen activator as compared to those with the Occlus-o-Guide(®).